2013
DOI: 10.1371/journal.pone.0068174
|View full text |Cite
|
Sign up to set email alerts
|

Ryanodine Receptors Selectively Interact with L Type Calcium Channels in Mouse Taste Cells

Abstract: IntroductionWe reported that ryanodine receptors are expressed in two different types of mammalian peripheral taste receptor cells: Type II and Type III cells. Type II cells lack voltage-gated calcium channels (VGCCs) and chemical synapses. In these cells, ryanodine receptors contribute to the taste-evoked calcium signals that are initiated by opening inositol trisphosphate receptors located on internal calcium stores. In Type III cells that do have VGCCs and chemical synapses, ryanodine receptors contribute t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…Isolated taste receptor cells were collected from adult mice (at ages 2, 6 or 12 months) following previously described procedures. 58, 59, 60, 61, 62, 63, 64, 65 Taste buds were harvested from CV and Fol papillae of C57BL/6 mice ( n =3 mice per sample for older mice, 4 mice per sample for 2 mo mice). Mice were killed with CO 2 and cervical dislocation.…”
Section: Methodsmentioning
confidence: 99%
“…Isolated taste receptor cells were collected from adult mice (at ages 2, 6 or 12 months) following previously described procedures. 58, 59, 60, 61, 62, 63, 64, 65 Taste buds were harvested from CV and Fol papillae of C57BL/6 mice ( n =3 mice per sample for older mice, 4 mice per sample for 2 mo mice). Mice were killed with CO 2 and cervical dislocation.…”
Section: Methodsmentioning
confidence: 99%
“…TRCs were harvested from taste papillae of adult mice as previously described . Briefly, tongues were removed and injected beneath the lingual epithelium with 0.2 mL of enzyme solution (3 mg of Dispase II, 0.7 mg of collagenase B [Roche Diagnostics, Indianapolis, Indiana], and 1 mg of trypsin inhibitor in 1 mL of Tyrode’s).…”
Section: Methodsmentioning
confidence: 99%
“…TRCs were harvested from taste papillae of adult mice as previously described (12,(20)(21)(22)(23)(24)(25). Briefly, tongues were removed and injected beneath the lingual epithelium with 0.…”
Section: Taste Cell Isolationmentioning
confidence: 99%
“…Further analysis found that in the TRCs with both VGCCs and the PLC signaling pathway, the ryanodine receptors were exclusively contributing to the calcium influx signal generated by VGCCs and no longer contributed to the calcium release signal generated by activating the PLC signaling pathway [30]. Data indicated that the ryanodine receptors were associating with L-type VGCCs in these cells and that there is a functional, but not physical interaction, between these proteins [31]. The mechanism underlying this selective interaction has not been identified in taste cells but this specificity may be due to the localization of these different signaling components on the endoplasmic reticulum.…”
Section: Calcium Signaling In Taste Cellsmentioning
confidence: 99%
“…The distribution of VGCCs in taste cells has not been well-characterized but studies have established that multiple VGCCs are expressed in taste cells, including L-type calcium channels. It is clear that L-type calcium channels are not the only VGCCs in taste cells [20, 31, 48, 49] and the Roberts et al (2009) study indicates that there is some segregation in the expression of VGCC isoforms within taste cells. If L-type calcium channel inactivation does significantly affect the amplitude of the response peak, then NCXs may actually have an important role in controlling the initial peak response magnitude that was not measured in the earlier study [46].…”
Section: Calcium Regulation In Taste Cellsmentioning
confidence: 99%